1988
DOI: 10.1002/pd.1970080202
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of tetrasomy 47,XY, + i(12p) confirmed by in situ hybridization

Abstract: A case of tetrasomy i(12p) detected prenatally is reported. The patient, a black, 32-year-old G3P2002 at 24 weeks' gestation with an unremarkable family history presented herself for prenatal care. Ultrasound examination showed a fetus with diminished femoral and humeral lengths, and hydramnios. A level II scan confirmed the presence of an omphalocele. Amniocentesis at 31 weeks showed 47,XY,+i(12p) karyotype. An infant with multiple congenital anomalies was delivered at 34 weeks. The infant died after 5 h. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…The marker chromosome was identified as an i(12p) using a cDNA probe for the KRAS2 gene, which maps to chromosome 12p12. A premature male infant with multiple congenital anomalies was born at 34 weeks, but died after 5 h (Shivashankar et al, 1988). A total of 20 cases have been diagnosed following amniocentesis for either AMA or detection of fetal anomalies (Gilgenkrantz et al, 1985;Lopes et al, 1985;Hunter et al, 1986;Steinbach and Rehder, 1987;Warburton et al, 1987, case 3;Shivashankar et al, 1988;Eydoux et al, 1989;Soukup and Neidich, 1990;Speleman et al, 1991, case 4;Blancato et al, 1991Blancato et al, , 1992McLean et al, 1992;Priest et al, 1992;Tejada et al, 1992;Bergoffen et al, 1993, case 3;Donnenfeld et al, 1993, cases 8 and 12;Larramendy et al, 1993;Wilson et al, 1994, cases 1 and 2; Los et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marker chromosome was identified as an i(12p) using a cDNA probe for the KRAS2 gene, which maps to chromosome 12p12. A premature male infant with multiple congenital anomalies was born at 34 weeks, but died after 5 h (Shivashankar et al, 1988). A total of 20 cases have been diagnosed following amniocentesis for either AMA or detection of fetal anomalies (Gilgenkrantz et al, 1985;Lopes et al, 1985;Hunter et al, 1986;Steinbach and Rehder, 1987;Warburton et al, 1987, case 3;Shivashankar et al, 1988;Eydoux et al, 1989;Soukup and Neidich, 1990;Speleman et al, 1991, case 4;Blancato et al, 1991Blancato et al, , 1992McLean et al, 1992;Priest et al, 1992;Tejada et al, 1992;Bergoffen et al, 1993, case 3;Donnenfeld et al, 1993, cases 8 and 12;Larramendy et al, 1993;Wilson et al, 1994, cases 1 and 2; Los et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal diagnosis has been previously reported in 23 cases of PKS (Gilgenkrantz et al, 1985;Lopes et al, 1985;Hunter et al, 1986;Steinbach and Rehder, 1987;Shivashankar et al, 1988;Eydoux et al, 1989;Soukup and Neidich, 1990;Bresson et al, 1991;Sharland et al, 1991;Speleman et al, 1991;Blancato et al, 1992;Bernert et al, 1992;McLean et al, 1992;Priest et al, 1992;Tejada et al, 1992;Bergoffen et al, 1993;Donnenfeld et al, 1993;Larramendy et al, 1993;Wilson et al, 1994;Los et al, 1995). Both chorionic villi and amniocytes appear to maintain the isochromosome; however, the level of mosaicism varies greatly between individuals.…”
Section: Introductionmentioning
confidence: 89%
“…The trisomy D [12][13][14][15] chromosomal anomaly exhibits variable Placental maturation, reduced villous vasculature and giant cytophoblast in 50% or more of villi [Table/ Fig-4]. Tetrasomy 12 is a well-recognised chromosomal error with usually lethal anomalies, severely malformed fetus with normal birth weight and essentially normal placenta [13]. Shepard et al, [14] undertook 20 y analysis of aborted specimen and found that 19% of fetus had a localized defect.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is identical to that described by Killian and Teschler-Nicola [19811. Subsequent examinations of patients with Teschler-Nicola Killian syndrome demonstrated the presence of aneuploid cell lines with an isochromosome 12p or additional chromosomal material derived from 12p [Buyse and Korf, 19831. Gene dosage studies of the LDH isoenzymes [Steinbach and Rehder, 1987;Warburton et al, 1987;Reynolds et al, 19871 and molecular hybridization with KRAS 2 probes [Peltomaki et al, 1987;Shivashankar et al, 1988;Zangh et al, 19891 provided additional evidence on the origin of the extra chromosome.…”
Section: Introductionmentioning
confidence: 97%